2017
DOI: 10.1111/dom.13102
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon receptor as a drug target: A witches' brew of eye of newt (peptides) and toe of frog (receptors)

Abstract: Glucagon has a noble history in the annals of metabolic disease, 1 even though, to a layperson, insulin is its more famous counterregulatory partner. For decades medical students have been taught that glucagon raises blood glucose by increasing hepatic glucose output and that alleviation of hypoglycaemia is its primary function. 2 Thus, inhibition of glucagon secretion 3 or action 4 are logical approaches to the development of therapeutics that improve glycaemic control in both type 2 and type 1 diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…However, several adverse effects of therapy have also been reported, including an increase in blood pressure, weight, plasma LDL-cholesterol and plasma transaminase concentrations. 11 While not measured with other compounds, a recent publication showed an increase in hepatic fat content with LY2409021, which was the first to correlate the transaminase increase with potential, underlying pathophysiology. 12 An additional concern is that chronic glucagon receptor blockade will cause pancreatic α-cell hyperplasia, which has been shown in animal models 13,14 and in case reports demonstrating α-cell hypertrophy and severe hyperglucagonaemia, without evidence of glucagonoma syndrome, in individuals with loss-of-function glucagon receptor mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several adverse effects of therapy have also been reported, including an increase in blood pressure, weight, plasma LDL-cholesterol and plasma transaminase concentrations. 11 While not measured with other compounds, a recent publication showed an increase in hepatic fat content with LY2409021, which was the first to correlate the transaminase increase with potential, underlying pathophysiology. 12 An additional concern is that chronic glucagon receptor blockade will cause pancreatic α-cell hyperplasia, which has been shown in animal models 13,14 and in case reports demonstrating α-cell hypertrophy and severe hyperglucagonaemia, without evidence of glucagonoma syndrome, in individuals with loss-of-function glucagon receptor mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have evaluated the effect of glucagon receptor blockade in humans by using small molecule antagonists, antisense oligonucleotide inhibitors of the glucagon receptor and monoclonal glucagon receptor antibodies . All of these approaches have consistently improved glycaemic control, manifested by a decrease in A1c and blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gcgr knockout mice displayed an antidiabetogenic effect in both T1D and T2D mice 22–25. Despite numerous compounds having been developed during the last two decades, most agents were discontinued for further development due to some unexpected adverse events 3 5. Therefore, developing a safe and efficacious GCGR antagonist remains highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon acts through the glucagon receptor (GCGR), which is a G protein-coupled receptor expressed in the liver as well as multiple extrahepatic tissues, including the gastrointestinal tract 2. Accumulating evidence proves that disruption of GCGR signaling, using gene knockout, antisense oligonucleotide, antagonists or antibodies, can alleviate hyperglycemia in animals and humans 3–5. Recent data from our group and others have shown that REMD 2.59, a fully competitive antagonistic human GCGR monoclonal antibody (mAb), has a strong hypoglycemic effect in type 1 diabetic (T1D) and T2D rodents and non-human primates 6–10.…”
Section: Introductionmentioning
confidence: 99%